2008
DOI: 10.1038/eye.2008.321
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of HRT II and AS-OCT to evaluate corneal endothelial cell loss and in vivo visualization of the Ahmed glaucoma valve implant

Abstract: Aims To report corneal endothelial cell loss and in vivo visualization of the Ahmed glaucoma valve implant in eyes with refractory glaucoma. Methods Ten eyes underwent Ahmed valve implant surgery and were followed-up for 12 months. Data collected included intraocular pressure (IOP

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 43 publications
1
34
2
Order By: Relevance
“…Guthoff et al 80 show that encapsulated blebs can be easily identified using AS-OCT, which provides information about the height of the bleb and the internal morphology, which can be used to identify blebs that are suitable for bleb needling. Furthermore, AS-OCT can be used to assess the patency and position of tubes after glaucoma drainage implant surgery ( Figure 14) 81 and is especially useful in patients with an opaque cornea or vulnerable cornea; for example, shortly after PKP. 82 Anterior segment OCT can also evaluate the effectiveness of iridotomies.…”
Section: Evaluation Of Glaucoma Surgerymentioning
confidence: 99%
“…Guthoff et al 80 show that encapsulated blebs can be easily identified using AS-OCT, which provides information about the height of the bleb and the internal morphology, which can be used to identify blebs that are suitable for bleb needling. Furthermore, AS-OCT can be used to assess the patency and position of tubes after glaucoma drainage implant surgery ( Figure 14) 81 and is especially useful in patients with an opaque cornea or vulnerable cornea; for example, shortly after PKP. 82 Anterior segment OCT can also evaluate the effectiveness of iridotomies.…”
Section: Evaluation Of Glaucoma Surgerymentioning
confidence: 99%
“…2008; Mendrinos et al. 2009; Hau & Barton 2009). Endothelial cell loss was reported after Molteno glaucoma drainage device (GDD) insertion (McDermott et al.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional ultrasonography, 6 ultrasound biomicroscopy, 7 and more recently, anterior segment optical coherence tomography (AS-OCT) have been used to locate tube position and patency within the eye. 8,9 The purpose of this cross-sectional study was to explore the relationship between corneal endothelial cell density with potential influences such as number of previous operations, type of glaucoma, and shunt position in the AC.…”
mentioning
confidence: 99%